A comparative study of physicochemical and functional properties of silver carp myofibrillar protein glycated with glucose and maltodextrin. Issue 2 (4th January 2017) - Liu, Shulai; Zhao, Peicheng; Zhang, Jingjing; Xu, Qiuhong; Ding, Yuting; Liu, Jianhua
Abstract : Myofibrillar protein (Mf) from silver carp ( Hypophthalmichthys molitrix ) was incubated with glucose and maltodextrin for 0–96 h at 50 °C and 75% relative humidity to obtain glycoconjugates in different periods of the Maillard reaction. Abstract : Myofibrillar protein (Mf) from silver carp ( Hypophthalmichthys molitrix ) was incubated with glucose and maltodextrin for 0–96 h at 50 °C and 75% relative humidity to obtain glycoconjugates in different periods of the Maillard reaction. Physicochemical properties, including molecular weight, sugars bound to Mf, available amino acid content and FT-IR properties all indicated that glycation occurred successfully. In addition, SDS-PAGE analysis and available amino acids of Maillard reaction productions (MRPs) suggested that glucose reacted more easily with Mf than maltodextrin. Functional properties of MRPs were superior to Mf and reached the highest value at 8–12 h, and then decreased significantly. Heat stability and solubility of Mf–maltodextrin in 0.5 M NaCl was better than for Mf–glucose, while the solubility in 0.1 M NaCl, and the emulsifying and foaming properties of Mf–glucose were in general better than for Mf–maltodextrin. The variety of saccharides and the process of the Maillard reaction had a great influence on the physicochemical and functional properties of MRPs.